Stress Factors and Way of Coping Amongst the Students of Medical College - Gore, Harishchandra D; Shelke, Ashok D; Mane, Abhay B; Nanaware4, Kartiki R; Gawade, Sachin A; Fernandez, Kevin (National Journal of Community Medicine, 2016)
Introduction: Medical profession, although a noble profession, is not spared from the stress and suicidal tendencies. Stress, if not dealt effectively, loneliness, nervousness, and sleeplessness is inevitable. The present study was undertaken to identify the stress factors and way of coping amongst medical student. Methods: Cross-sectional study was done on 353 medical students using pretested, semi structured questionnaire. Information regarding Personal data, Stress inducing factors & ways of coping was collected from the participants. Results: Medical students that reported stress factors were course material of MBBS by 71.7%, followed by economic problems 60.7%, academic factors 57.0%, competition in college 56.6%, college/hostel environmental factors 44.9% and social problems 39.5%. Individual stress factors in decreasing order were work overload in 80.5%, nervous breakdown before or during viva 79.3%, worry for Postgraduate seat 75.1%, fear of failure in exam in 72.8% students. Only 19.8% students had stress due to ragging. Talking to friends (79%), call at home or go to home or movie (50-53%) & using internet/ videogames (50%), were major way of coping. Conclusions: The major stressors identified were academic factors and course material. The preferred method of coping was talking to friends and family members.